Модель акустичної томографії з врахуванням відбиття та викривлення траєкторій звукових хвиль - Головко, Владислав Олексійович; Медведєв, Дмитро Геннадійович (НТУ "ХПІ", 2015)
Особливість запропонованого підходу полягає в апроксимації області зондування в томографії білінійним сплайном, який регуляризує розв’язок. Мета полягає у відновленні внутрішньої структури досліджуваного об’єкту. При зондуванні суттєво неоднорідного середовища відбувається відбиття й викривлення шляху зондування. Викривлення променю апроксимуємо ламаною, враховуючи зміни швидкості на границях сітки сплайна. Вирішено пряму і обернену томографічну задачу для даної моделі. Проведено ряд експериментів з різним значенням шуму.

The object of study is the forward and inverse tomography problems. The peculiarity of the proposed approach consists in approximating of the sensing field of tomography by bilinear spline, which regularized solution. The aim is to restore the internal structure of an object, including irregularities it contains. In case of probing of substantially non-homogeneous media, the reflection and refraction of the probe path will occur in the medium. This paper proposes the model which takes into account reflection and refraction of sound wave. The beam refraction is approximated with the polyline taking into consideration the velocity variation at the boundaries of the spline grid. The direct and inverse tomography problems were solved for this model. A number of experiments with different noise values have been carried out. The impact of noise on error of values recovery in the nodal points has been analyzed.
Acoustic tomography model which takes into account reflection and refraction of sound wave paths
Keywords: рефракція; білінійний сплайн; неруйнівний контроль; пряма томографічна задача; обернена томографічна задача; bilinear spline; non-destructive testing